216k views
5 votes
Suppose that F(x)=x^3 and G(x)=-2x^3

Suppose that F(x)=x^3 and G(x)=-2x^3-example-1

2 Answers

3 votes

Answer:

it is answer A

Explanation:

Ap*x

User Arty
by
6.1k points
2 votes

Answer:

A

Explanation:

Given a function f(x) = x^2, we can say:

  • g(x) = -(x^2) is the reflection of f(x) in the x-axis
  • h(x) = ax^2 is a vertical stretch if a > 1 and a vertical compression if 0 < a < 1

The negative sign in front says that G(x) is flipped over the x-axis with respect to F(x). Also, the 2 in front tells us that it is a vertical stretch of the function F(x), since a > 1.

Hence, answer choice A is right.

User Rafael Rocha
by
5.6k points